Antimetastatic effect of intratumoral Treg antagonists in mice with renal cancer - Gulyás, Dominik; Kovács, Gábor; Jankovics, István; Hidvégi, Máté; Dénes, Béla; Kálfalvy-Molnár, Lilla; Nagypál, Rebeka; Lőrincz, Márta (Acta veterinaria Hungarica (Budapest. 1983), 2024)
The interplay of regulatory T cells (Tregs) within the tumour microenvironment presents a significant challenge in anticancer immunotherapy. This study investigates the potential of Treg blockade to enhance the efficiency of effector T cells. Two distinct treatment cocktails were examined: 3p-hpRNA (5' triphosphate hairpin RNA) combined with unmethylated CpG oligonucleotide (CpG); CpG in combination with OX40 receptor-specific monoclonal antibody (anti-OX40). Treatment efficacy was assessed using a murine model of kidney adenocarcinoma.Renca cells (renal cortical cells with adenocarcinoma) were subcutaneously engrafted in 30 BALB/c mice, then animals were allocated into three treatment groups: Group 1: CpG+anti-OX40, Group 2: CpG+3p-hpRNA, Group 3: untreated control. Treatment efficacy was evaluated based on tumour growth, the occurrence of metastases and overall survival.On day 28 post-implantation, experiments had to be terminated due to tumour progression. Although comparisons of survival times and primary tumour sizes thus became inconsequential, histological examinations provided valuable insights. We observed distinct variations in primary tumour characteristics among the different groups: Groups 1 and 2 displayed demarcations, while Group 3 exhibited diffuse tumours with necrosis. Lung metastases were evident in 70% of untreated mice, whereas none were observed in either of the treated groups.Our findings instil confidence in the potential efficacy of the treatments, thereby laying a solid foundation for future investigations.